SIKAP MASYARAKAT DUSUN PASIR LAUT TERHADAP PENETAPAN OBYEK WISATA MANGROVE DI DESA PASIR KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Agus Syafarudin; Sudirman Muin; . Fahrizal (Tengkawang : Jurnal Ilmu Kehutanan, 2017)
Utilization of the natural resources potential of flora and fauna as well as its environmental services in the area of natural tourism refers to the principles of social forest management in its utilization based on ecological, social and economic sustainability. the development of the needs of natural tourism, the natural conservation areas such as National Parks, Forest Parks and Nature Parks. Methods of data collection is done by interview technique assisted by questionnaire tool which submitted to the respondent. The respondent collected by purposive sampling is technique of determining sample with certain consideration. Result of research indicate that society attitude toward determination of mangrove area become tourism object 85 respondent tend to Neutral equal to 62,35%, 08,23% Tend to Reject and Receive equal to 29,42%. Community attitude tend to be neutral to Stipulation of Tourism Object of Mangrove Forest area. This proves that the Sea Dusun Pasir Laut supports or accepts with the determination of tourism objects in the mangrove forest. People who have an attitude tend to accept are people who have a high level of concern for the sustainability of the mangrove forest without ignoring the principle of sustainability.Keywords: Community Attitude, of Tourism Object, Mangrove Forest Area